RESPON ESTRUS DOMBA GARUT BETINA PADA PERLAKUAN LASERPUNTUR DENGAN FASE REPRODUKSI YANG BERBEDA - herdis, herdis (Badan Pengkajian dan Penerapan Teknologi, 2011)
The research was carried out to assess the technology of laserpuncture for estrous synchronization of ewes in different phase reproduction. The results of the research showed that the treatment of laserpuncture at 17 reproduction accupoints during the luteal phase and at anytime perform 100% and 95% of oestrous, respectively. It indicates that the laserpunktur technology is capable to generates a synchronization of oestrus in ewes. There was no significant difference of oestrus response which observed from both of treatments at luteal phase or at any time. It is concluded that the laserpuncture technology is one of alternative technology for estrous synchronization beside hormone treatment.